The Millennials’ Effect: How Can Their Personal Values Shape the Future Business Environment of Industry 4.0? - Črešnar, Rok; Jevšenak, Senta (Naše gospodarstvo/Our economy, 2019)
The main purpose of this paper is to assess a possible impact millennials will have on the future business environment of Industry 4.0, based on their personal value orientations. Millennials are taking over important roles in organizations, but their personal values are significantly different from those of older generations. This paper shows that, based on the Schwartz’s value survey with N=371 Slovenian respondents, millennials are in general more inclined toward values connected to personal growth and freedom from anxiety, emphasizing self-transcendence and openness to change, than toward self-protection and anxiety avoidance, understating conservation and self-enhancement values. These cognitions can have significant implications in shaping the future business environment of Industry 4.0, as it can become more open, understanding, collaborative, accepting, and generally more supporting, thus creating the evident millennials’ effect. Even though millennials are in general well prepared for the future business environment, organizations will have to, in order to retain the millennials, reshape their current organizational environment to better reflect the millennials’ views.